Management of recurrent rectal prolapse: surgical approach influences outcome - Steele, Scott R; Goetz, Laura H; Minami, Shigeki; Madoff, Robert D; Mellgren, Anders F; Parker, Susan C (Diseases of the colon & rectum, 2006)
Recurrent rectal prolapse is an unresolved problem and the optimal treatment is debated. This study was designed to review patterns of care and outcomes in a large cohort of patients after surgery for recurrent prolapse. From 685 patients who underwent operative repair for full-thickness external rectal prolapse, we identified 78 patients (70 females; mean age, 66.9 years) who underwent surgery for recurrence. We reviewed the subsequent management and outcomes for these 78 patients. Mean interval to their first recurrence was 33 (range, 1-168) months. There were significantly more re-recurrences after reoperation using a perineal procedure (19/51) compared with an abdominal procedure (4/27) for their recurrent rectal prolapse (P = 0.03) at a mean follow-up of nine (range, 1-82) months. Patients undergoing abdominal repair of recurrence were significantly younger than those who underwent perineal repair (mean age, 58.5 vs. 71.5 years; P < 0.01); however, there was nosignificant difference between the two groups with regard to the American Society of Anesthesiologists classification (P = 0.89). Eighteen patients had surgery for a second recurrence, with perineal repairs associated with higher failure rates (50 vs. 8 percent; P = 0.07). Finally, when combining all repairs, the abdominal approach continued to have significantly lower recurrence rates (39 vs. 13 percent; P < 0.01). The re-recurrence rate after surgery for recurrent rectal prolapse is high, even at a relatively short follow-up interval. Our data suggest that abdominal repair of recurrent rectal prolapse should be undertaken if the patient's risk profile permits this approach.